Kursi Roda Otomatis Line Follower Dikontrol menggunakan Android Berbasis (Internet Of Things) IoT - Kurniawan, Simplisius Yekri; Setiawan, Aries Boedi; Dirgantara , Wahyu (Program Studi Teknik Elektro - Fakultas Teknik - Universitas Widyagama Malang, 2023)
A wheelchair is a mobility aid for people who have special needs, one of which is a disability. Usually this wheelchair is in the form of a manual wheelchair, which requires the help of another person to push the wheelchair. However, as time and technology have progressed, many studies have designed wheelchairs to be electric so that users will find it easier. This study aims to make new innovations so that users do not have difficulty using a wheelchair by controlling the wheelchair using a smartphone so that users are more comfortable. The components we use are a 12 v power windod motor as the ESP32 wheel drive for microcontrollers, line sensors to read ultrasonic sensor paths for detecting obstacles and the blynk application for monitoring the wheelchair thoroughly. the designer for IoT on this wheelchair can carry a large load of 80 kg with a distance of 20m and for how to control this wheelchair depends on the network